Base excision repair targets for cancer therapy - Dianov, Grigory L (e-Century Publishing Corporation, 2011)
Cellular DNA repair is a frontline system that is responsible for maintaining genome integrity and thus preventing premature aging and cancer by repairing DNA lesions and strand breaks caused by endogenous and exogenous mutagens. However, it is also the principal cellular system in cancer cells that counteracts the killing effect of the major cancer treatments e.g. chemotherapy and ionizing radiation. The major goal of this review is to critically exam the base excision repair pathway and mechanisms regulating base excision repair capacity as a potential targets for improving cancer therapy.